Pengaruh Ukuran Perusahaan dan Profitabilitas Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di BEI ( ALTO, CEKA, STTP, ICBP, INDF,ROTI, ULTJ, MYOR ) Periode Tahun 2016-2019 - Amanda Awalia; Nanu Hasanuh (Tirtayasa Ekonomika, 2022)
All food and beverage sector companies listed on the BEI in the period 2016 to 2019 are included in the sample of this study. Purposive sampling method with special criteria was used to take research samples from 51 organizations, resulting in a sample size of up to 8 companies. In contrast to profitability, the data testing approach uses linear regression with results showing that firm size does not substantially affect firm value. Profitability has a beneficial and specific impact on firm value. Simultaneously, firm size and profitability have a favorable impact on firm value. The coefficient of determination shows that firm size and profitability have an 83.3 percent effect on firm value, with other balances being dominated by other factors.